Humeral Condylar Fractures in French Bulldogs: Prevalence of Contralateral Intracondylar Fissure, Treatment, and Outcome - Lopez de la Oliva, Paula; Arnott, Luke; Roses, Leonor; Marshall, William; Arnott, Davinia (Veterinary and Comparative Orthopaedics and Traumatology, 2024)
Objective The aim of this study was to report (1) the prevalence of contralateral humeral intracondylar GAP/HIF (HIF) in French Bulldogs with humeral condylar fractures (HCF) and (2) treatment and short- and long-term outcome in French Bulldogs with HCF.Materials and Methods Medical records of French Bulldogs treated surgically for HCF between January 2011 and November 2022 were reviewed. Perioperative imaging, surgical technique, complications, and long-term outcome were assessed.Results Eighty-nine dogs with HCF were included and 36/89 were diagnosed with HIF. Surgical repair was performed in all HCF and a prophylactic transcondylar screw was placed in 20/36 HIF. For prophylactic transcondylar screw placement, two dogs required immediate revision surgery. Complications occurred in 12/89 HCF, and there were major complications in 6/89 HCF. Long-term outcome evaluated by owner questionnaire (n = 27) was rated as being excellent in 18/27 dogs, good in 8/27 dogs, and fair in 1/27 dogs.Clinical Significance Forty percent of French Bulldogs with HCF had a contralateral HIF. HIF as a cause of HCF should be considered in the French Bulldog, and a computed tomography (CT) scan of both elbows may be advisable prior to HCF repair. The complication rate of HCF surgery in the French Bulldog is significant.
Keywords: elbow; incomplete ossification; French Bulldog; lameness; stress fracture